"Hit‐and‐Run" leaves its mark: Catalyst transcription factors and chromatin modification. (23rd June 2015) - Varala, Kranthi; Li, Ying; Marshall‐Colón, Amy; Para, Alessia; Coruzzi, Gloria M.
<x xml:space="preserve">Abstract</x> Understanding how transcription factor (TF) binding is related to gene regulation is a moving target. We recently uncovered genome‐wide evidence for a "Hit‐and‐Run" model of transcription. In this model, a master TF "hits" a target promoter to initiate a rapid response to a signal. As the "hit" is transient, the model invokes recruitment of partner TFs to sustain transcription over time. Following the "run", the master TF "hits" other targets to propagate the response genome‐wide. As such, a TF may act as a "catalyst" to mount a broad and acute response in cells that first sense the signal, while the recruited TF partners promote long‐term adaptive behavior in the whole organism. This "Hit‐and‐Run" model likely has broad relevance, as TF perturbation studies across eukaryotes show small overlaps between TF‐regulated and TF‐bound genes, implicating transient TF‐target binding. Here, we explore this "Hit‐and‐Run" model to suggest molecular mechanisms and its biological relevance.